Distribution and abundance of wintering raptors in the Korean peninsula - Sang-don Lee (Journal of Ecology and Environment, 2013)
The purpose of this study is to examine distribution and abundance of wintering raptors in Korea during 2000-2007 which is a rare data set for covering large landscape areas. Total 6,643 raptors of 16 species were recorded at 94 different points in west, south and east coasts, and rivers of inland areas all over Korea. During the study period, the most abundant raptors were black vulture (Aegypius monachus, 62.3%), common kestrel (Falco tinnunculus, 11.0%) and common buzzard (Buteo buteo, 10.0%), and these 3 birds were dominant species in inland areas and also considered as resident species except for black vulture. Also, there was a difference among 5 different habitat types. Black vultures were most found in estuaries whereas common buzzard and common kestrel could be found in coastal areas. Presumably raptors prefer reservoirs and estuaries probably due to lower human disturbance in these areas, and management efforts should be concentrated in inland areas for black vulture and coastal areas for common kestrel and common buzzard.